2010
DOI: 10.1016/j.jsat.2009.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Incentives for retention of pregnant substance users: A secondary analysis

Abstract: Retention of pregnant substance users in treatment is challenging. In a multi-site clinical trial, 200 pregnant substance users entering outpatient treatment at 1 of 4 programs were randomized to either 3 individual sessions of Motivational Enhancement Therapy for Pregnant Substance users (MET-PS) or 3 individual sessions normally provided. Retail scrip from $25 to $30 was provided for attendance of research visits but not treatment visits. A post-hoc analysis of the non-methadone maintained participants (N=17… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 24 publications
1
13
0
1
Order By: Relevance
“…A post-hoc evaluation of the possible effect of financial incentives on visit attendance in non-methadone-maintained MET-PS participants (N=175) compared attendance at monetarily reinforced research visits ($25-30 retail scrip per visit) to attendance at non-incentivized treatment sessions [21]. Consecutive and overall weeks of attendance for incentive-reinforced research visits were significantly better than attendance at treatment sessions with no financial incentives.…”
Section: 0 Resultsmentioning
confidence: 99%
“…A post-hoc evaluation of the possible effect of financial incentives on visit attendance in non-methadone-maintained MET-PS participants (N=175) compared attendance at monetarily reinforced research visits ($25-30 retail scrip per visit) to attendance at non-incentivized treatment sessions [21]. Consecutive and overall weeks of attendance for incentive-reinforced research visits were significantly better than attendance at treatment sessions with no financial incentives.…”
Section: 0 Resultsmentioning
confidence: 99%
“…This is an important consideration that is particularly salient in the perinatal period. Alternate, less coercive methods of promoting receipt of needed services should be carefully considered, including motivational approaches (Handmaker and Wilbourne, 2001; Jones et al, 2004) and contingency management (Brigham et al, in press; Jones et al, 2001; Jones et al, 2000). The extent to which existing treatment programs can be made more relevant and attractive to women using substances during pregnancy should also be considered.…”
Section: 0 Discussionmentioning
confidence: 99%
“…Higgins and Petry (1999), in a review of the use of CM in substance abuse treatment, found that in addition to reducing substance use, CM may be useful in improving treatment attendance. More recently, CM research directed at substance abuse treatment retention or attendance has expanded into a variety of settings and formats, including inpatient, outpatient, methadone, telephone or in-person treatment and rehabilitative programs such as job skills training; and with a variety of populations (pregnant women, youth dependent on marijuana, veterans, methadone users, general populations in community outpatient treatment, and dually diagnosed) (Alessi, Hanson, Weiners & Petry, 2007; Bride & Humble, 2008; Brigham, Winhusen, Lewis, & Kropp, 2010; Businelle, Rash, Burke, & Parker, 2009; Carroll et al, 2006; Helmus, Saules, Schoener & Roll, 2003; Jones, Haug, Stitzer & Svikis, 2000; Jones, Haug, Silverman, Stitzer & Svikis, 2001; Ledgerwood, Alessi, Hanson, Godley & Petry, 2008; Rhodes et al, 2003; Sinha, Easton, Renee-Aubin & Carroll, 2003; Walker et al, 2010). In general, research on CM for treatment attendance has shown mixed effectiveness results--some studies show promising results, while some are hampered by design issues such as non-random assignment, attrition, and post-hoc analysis (Brigham et al, 2010; Businelle et al, 2009; Ledgerwood et al, 2008; Rhodes et al, 2003).…”
Section: Introductionmentioning
confidence: 99%